The Influence of Islamic Values on Nigerian Education and Culture - Ismaila Boladale Lawal (CV Media Inti Teknologi, 2025)
Background of Study: This paper explores the profound influence of Islamic values on Nigerian education and culture. With a significant Muslim population, Nigeria’s educational system and cultural practices have been shaped by Islamic principles. This research examines the historical context of Islam in Nigeria, tracing its spread and impact on education and culture. Aims and Scope of Paper: The study analyzes the difficulties facing Islamic education and culture in Nigeria and explores the ways in which Islamic beliefs have impacted Nigerian education and culture.Methods: In order to provide a comprehensive knowledge of how Islamic beliefs impact Nigerian education and culture, the study methodically explores pertinent texts and documents using a qualitative approach with content analysis.Result: The outcome shows that Islamic principles have had a major influence on Nigerian education, influencing curricula, instructional strategies, and student conduct. Islamic principles have impacted creative expression, communal harmony, and societal conventions. The study does, however, also highlight issues with Islamic culture and education in Nigeria. This includes striking a balance between traditional Islamic values and modernization and secular influences; inadequate funding, infrastructure, and qualified teachers for Islamic schools; unfavorable opinions and misconceptions regarding Islamic values and education; and Muslim students' lack of access to high-quality Islamic education.Conclusion: The study comes to the conclusion that Islamic principles are fundamental to Nigerian culture and education, and their influence can be seen in many facets of Nigerian society.